Hydrochemistry and weathering rates on Corumbatai River basin, São Paulo State, Brazil - Bonotto, Daniel Marcos [UNESP]; Nepomuceno de Lima, Jorge Luis (Elsevier B.V., 2010)
This work was held at the Corumbatai River basin that is inserted within the giant Parana sedimentary basin (Paleozoic-Cenozoic) in South America. The Corumbatai River is the major river draining the area and its water is extensively used by water supply systems in the basin. Its surface waters were collected at two sampling points, upstream and downstream from Rio Claro city, the principal municipality within the basin. We report chemical and radionuclides ((222)Rn and (210)Po) analyses for rainwater and river water samples in order to estimate chemical weathering fluxes. All major chemical data indicated poorer conditions of the water quality in Corumbatai River after reaching Rio Claro city. However, one very important finding was that the weighted mean of the (210)Po activity concentration is the same (0.21 dpm/L) upstream and downstream from Rio Claro city, indicating that (210)Po is a conservative nuclide. The net output flux in Corumbatai River basin estimated from the difference between the total discharge flux and the input flux based on wet precipitation yielded a negative value for polonium as it is a very particle-reactive radionuclide, tending to accumulate into fluvial sediments. The chemical weathering rate (removed material quantity) corresponded to 76.5 t/km(2) yr when Po data in sediments and rocks were utilized in the calculations. This rate is compatible with others determined elsewhere, indicating the usefulness of Po in studies of weathering processes, even in areas characterized by anthropogenic inputs. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Hydrochemistry; Rainwater; Surface water; Weathering rate; Corumbatai River basin